2022
DOI: 10.3389/fnagi.2022.834319
|View full text |Cite
|
Sign up to set email alerts
|

Topological Alterations of the Brain Functional Network in Type 2 Diabetes Mellitus Patients With and Without Mild Cognitive Impairment

Abstract: The aim of this study was to explore the topological alterations of the brain functional network in type 2 diabetes mellitus (T2DM) patients with and without mild cognitive impairment (MCI) using resting-state functional magnetic resonance imaging (rs-fMRI) and graph theory approaches. In total, 27 T2DM patients with MCI, 27 T2DM patients without MCI, and 27 healthy controls (HCs) underwent rs-fMRI scanning. The whole-brain functional network was constructed by thresholding the Pearson’s correlation matrices o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Previous studies on topological alterations of the brain functional network showed that DMCI patients had considerably higher global and local efficiency, as well as multiple nodal centralities, compared to HCs. However, the topological properties of the entire brain network did not display any significant abnormalities among DMCN patients ( 34 ). The difference may be attributed to methodological and/or clinical factors.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies on topological alterations of the brain functional network showed that DMCI patients had considerably higher global and local efficiency, as well as multiple nodal centralities, compared to HCs. However, the topological properties of the entire brain network did not display any significant abnormalities among DMCN patients ( 34 ). The difference may be attributed to methodological and/or clinical factors.…”
Section: Discussionmentioning
confidence: 91%
“… Xiong et al (2020) showed that compared to T2DM with normal cognition function, T2DM with cognitive impairment group had a higher clustering coefficient and local efficiency, as well as increased nodal properties (efficiency, degree, and betweenness) in the parietal, temporal, and occipital lobes, but decreased in the right inferior temporal gyrus. On the other hands, according to Zhou et al (2022) , there were no significant differences in the global and nodal properties between the T2DM patients with and without cognitive impairment. Briefly, the complex alterations in the topological properties of functional brain networks in patients with T2DM are uncertain, and their correlation to cognitive function is unclear.…”
Section: Introductionmentioning
confidence: 76%
“…The small-world properties, global properties, and local properties of brain networks will be analyzed using graph theory. There are five small-world properties: clustering coefficient (Cp), characteristic path length (Lp), normalized clustering coefficient (Gamma, γ), normalized characteristic path length (Lambda, λ), and small-worldness (Sigma, σ) ( 50 , 51 ). A network is regarded to have small-world features when γ >> 1, λ ≈1, and σ > 1 ( 48 , 52 ).…”
Section: Methodsmentioning
confidence: 99%